ANALISIS PENGARUH ASPEK DEMOGRAFI, STATUS SOSIAL EKONOMI DAN PENGALAMAN KERJA TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI DENGAN LOVE OF MONEY SEBAGAI VARIABEL INTERVENING - Erika Radina Sipayung; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
This research is the development of previous study conducted by Elias (2010) by adding two dependent variable which art social economic status and work experience. This study aims to analize the influence of  several demographic, social economic status, and work experience to the accounting students ethical perception throught love of money as intervening variable.This research using undergraduated accounting students, PPA and master of accounting students of University of Diponegoro as a sample. The number of samples that used were 92 respondens. This research used convenience sampling to choosed the sample. The data obtained were analyzed by using PLS analysis technique (Partial Least Square) through the smartPLS software.The result showed that age, and gender has no significant influence with love of money. Gender just has influence with accounting students ethical perception. While education level, social economic status, and work experience has influances with love of money. Love of money has significant influences with accounting students ethical perception. But, the influence of a direct relationship between gender with accounting students ethical perception is greater than the effect on love of money. So the love of money cannot be said to be intervening variable.